2019
DOI: 10.1186/s13000-019-0786-4
|View full text |Cite
|
Sign up to set email alerts
|

Pathological diagnosis of thyroid nodules based on core needle biopsies: comparative study between core needle biopsies and resected specimens in 578 cases

Abstract: BackgroundPathological diagnosis based on core needle biopsy (CNB) should be different from a resected specimen because it is difficult to apply the histological criteria established for resected specimens to CNB due to sampling limitations. A pathological classification for thyroid nodule on CNB was first proposed by the Korean Group in 2015. The objective of this study was to test the reliability and clinical value of this proposal.MethodsAccording to the Korean proposal, the CNB diagnoses were categorized i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 17 publications
0
9
0
2
Order By: Relevance
“…The indeterminate rate of diagnosis is reported to be 10%-40% for FNB and 5%-20% for CNB[5]. Our comparative study between CNB and resected specimens of thyroid nodules showed that 74 of 578 cases were unable to be determined as malignant or benign based on CNB sample morphology alone[6]. The reason is that only follicles visible on CNB in addition to the presence of atypical nuclei and the absence of normal tissue as background makes it impossible to differentiate FTC, FVPTC, and CPTC with a follicular predominant growth pattern from FA, nodular hyperplasia and thyroiditis.…”
mentioning
confidence: 69%
See 1 more Smart Citation
“…The indeterminate rate of diagnosis is reported to be 10%-40% for FNB and 5%-20% for CNB[5]. Our comparative study between CNB and resected specimens of thyroid nodules showed that 74 of 578 cases were unable to be determined as malignant or benign based on CNB sample morphology alone[6]. The reason is that only follicles visible on CNB in addition to the presence of atypical nuclei and the absence of normal tissue as background makes it impossible to differentiate FTC, FVPTC, and CPTC with a follicular predominant growth pattern from FA, nodular hyperplasia and thyroiditis.…”
mentioning
confidence: 69%
“…Published studies have shown that the accuracy of CNB for the preoperative diagnosis of thyroid nodules was higher than that of FNB [5]. However, approximately 5%-20% of CNB samples are classified as indeterminate based on morphology alone [5,6]. Compared to FNB, samples collected by CNB are more accessible for various testing methods.…”
Section: Introductionmentioning
confidence: 99%
“…Ñë³ä çàóâàaeèòè, ùî ó ïàö³ºíò³â ³ç âóçëîâèì çîáîì òàêîae ïîòð³áíî ïðîâåñòè äîñë³äaeåííÿ ð³âíÿ ñèðîâàòêîâîãî êàëüöèòîí³íó ç ìåòîþ âè-êëþ÷åííÿ ìåäóëÿðíîãî ðàêó ÙÇ: öÿ ôîðìà ðàêó òðàïëÿºòüñÿ ó 04-1,4% âñ³õ çëîÿê³ñíèõ íîâîóòâîðåíü ó ÙÇ, à â 20-30% -öå ñ³ìåéíà (ñïàäêîâà) ôîðìà, ùî ñóïðîâîäaeóºòüñÿ äîñèòü ðàíí³ì â³ääàëåíèì ìåòàñòàçóâàííÿì. Äëÿ äèôåðåíö³éíî¿ ä³à´íîñòèêè õâîðèõ ³ç äîá-ðîÿê³ñíèìè àáî çëîÿê³ñíèìè âóçëàìè çàñòîñîâóþòü óëüòðàñîíî´ðàô³þ (ÓÑ¥) [4,8,11], òîíêîãîëêîâó àñï³ðàö³éíó á³îïñ³þ (ÒÀÏÁ) ³ç ïîäàëüøèì öèòîëî´³÷íèì äîñë³äaeåííÿì ïóíêö³éíîãî ìàòåð³àëó [4] àáî ïóíêö³þ ãîëêàìè á³ëüøîãî ä³àìåòðó ç îòðèìàííÿì ìàòå-ð³àëó äëÿ ã³ñòîëî´³÷íîãî äîñë³äaeåííÿ [20]. Çà äîïîìîãîþ óëüòðàçâóêîâî¿ êîëüîðîâî¿ äîï-ïëåðî´ðàô³¿ âèçíà÷àþòü âàñêóëÿðèçàö³þ ïà-ðåíõ³ìè ÙÇ, à òàêîae îñîáëèâîñò³ âàñêóëÿðè-çàö³¿ âóçë³â.…”
Section: ëàáîðàòîðíà òà ³íñòðóìåíòàëüíà ä³à´íîñòèêà âóçëîâîãî çîáàunclassified
“…Íàéá³ëüø âàaeëèâèì ³ åôåêòèâíèì ìåòîäîì ïðè îáñòåaeåíí³ ïàö³ºí-ò³â ³ç âóçëîâèì çîáîì (äîáðîÿê³ñíèì àáî çëî-ÿê³ñíèì) º ÒÀÏÁ ç ïîäàëüøèì öèòîëî´³÷íèì äîñë³äaeåííÿì [4,9]. ÒÀÏÁ âóçë³â ÙÇ ç öèòî-ëî´³÷íèì äîñë³äaeåííÿì ïóíêö³éíîãî ìàòåð³àëó äîçâîëÿº ïðîâåñòè äèôåðåíö³éíó ä³à´íîñòèêó äîáðîÿê³ñíèõ ³ çëîÿê³ñíèõ íîâîóòâîðåíü ÙÇ òà óíèêíóòè íåáàaeàíèõ îïåðàòèâíèõ âòðó÷àíü ó ïàö³ºíò³â ³ç äîáðîÿê³ñíèìè âóçëàìè [2,10,20]. Çà äàíèìè ÷èñëåííèõ äîñë³äaeåíü, ÷óòëèâ³ñòü ÒÀÏÁ ³ç öèòîëî´³÷íèì äî-ñë³äaeåííÿì âèÿâëåííÿ ðàêó ñòàíîâèòü 70-98% (â ñåðåäíüîìó áëèçüêî 80%), à ñïåöèô³÷-í³ñòü -70-100% (ó ñåðåäíüîìó 92%) [4].…”
Section: ïðîô³ëàêòèêàunclassified
“…[2][3][4][5][6][7][8] Unlike FNA, which has been validated as a standard diagnostic method for over half a century, the value of CNB has not yet been fully evaluated for diagnosing thyroid nodules. [9][10][11] The main limitation of FNA is nondiagnostic and indeterminate results, corresponding to categories I, III, and IV of the Bethesda System for Reporting Thyroid Cytopathology (BSRTC). 12 To overcome this weakness, some investigators have suggested CNB as alternative or complementary diagnostic tool for thyroid nodules, 5,8,[13][14][15][16] even though CNB does not show superior diagnostic performance to FNA for diagnosing thyroid cancer and poses a higher rate of post-biopsy hematoma than FNA.…”
Section: Introductionmentioning
confidence: 99%